2014
DOI: 10.1603/ec13298
|View full text |Cite
|
Sign up to set email alerts
|

Perching Mate-Locating Strategy in <I>Paysandisia archon</I> (Lepidoptera: Castniidae): Behavioral and Morpho-Physiological Investigations

Abstract: We studied Paysandisia archon (Burmeister) (Lepidoptera: Castniidae: Castniinae) courtship behavior to provide a detailed qualitative and quantitative description of male and female behaviors. Moreover, to investigate the role of antennal olfaction and visual stimuli in mate-recognition, bioassays with antennectomized adults and dummies were performed. To assess the presence of a pheromone gland in the ovipositor, morphological (using light and scanning electron microscopic techniques), electrophysiological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…A likely perching mate-locating behavior is performed by males; females trigger the courtship sequence by approaching perching males, which then pursue the females (Delle-Vedove et al 2014;Riolo et al 2014). Female courtship solicitation has also been observed in Pieridae (Rutowski 1980;Daniels 2007) and Nymphalidae (Bergman et al 2007) species.…”
Section: Courtship Behaviormentioning
confidence: 98%
See 3 more Smart Citations
“…A likely perching mate-locating behavior is performed by males; females trigger the courtship sequence by approaching perching males, which then pursue the females (Delle-Vedove et al 2014;Riolo et al 2014). Female courtship solicitation has also been observed in Pieridae (Rutowski 1980;Daniels 2007) and Nymphalidae (Bergman et al 2007) species.…”
Section: Courtship Behaviormentioning
confidence: 98%
“…Detailed qualitative and quantitative descriptions of P. archon male and female reproductive behavior have been reported in two recent studies showing that the courtship is a sequence of stereotyped behavioral steps (Delle-Vedove et al 2014;Riolo et al 2014). A likely perching mate-locating behavior is performed by males; females trigger the courtship sequence by approaching perching males, which then pursue the females (Delle-Vedove et al 2014;Riolo et al 2014).…”
Section: Courtship Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…In outdoor experiments, mating peaks between 1400 h and 1500 h, and 87% of the females are fertilized and start laying eggs 1.25 (±1.14) days after mating (Delle Vedove et al 2012). Riolo et al (2014) reported that in semi field conditions mating occurred mainly in the morning from 0930 to 1130 h; mated moths were 1-2 days old. Under laboratory conditions, mating occurred in the afternoon, as soon as the cage with males and females was in the sun (Beaudoin-Ollivier, unpublished).…”
Section: Life Cyclementioning
confidence: 99%